The political potency of the black woman's voice: A discourse analysis of songs by Elza Soares (TEL Tempo, Espaço e Linguagem, 2024)
This article aims to interpret the meanings constituted in the lyrics of the albums A Mulher do Fim do Mundo (2015), Deus é Mulher (2018) and Planeta Fome (2019) by Elza Soares, in order to understand the political power of the black woman's voice. The main argument adopts the understanding that the singer's songs are a form of theorizing engaged knowledge and a social practice, both embodied in an intersectional political stance. The analysis was conducted with the application of Norman Fairclough's (2003) textually oriented discourse analysis method, based on the operation of four analytical categories: embodiment, resilience/insubordination, self-definition and empowerment.